Antenatal diagnosis of Patau syndrome with previous anomalous baby - Kocherla, Keerthi; Kocherla, Vasantha (International Journal of Research in Medical Sciences, 2017)
Patau syndrome is the least common and most severe of the viable autosomal trisomies with median survival of fewer than 3 days was first identified as a cytogenetic syndrome in 1960. Patau syndrome is caused by an extra copy of chromosome 13. In this case report, we present antenatal imaging findings & gross foetal specimen correlation of foetus with Patau syndrome confirmed by karyotyping in third gravida who had significant previous obstetric history of gastrochisis in monochorionic and monoamniotic twins who died at 14 weeks of gestation.